The role of serum catestatin in lipid metabolism disorders in patients with coronary artery disease and chronic heart failure depending on concomitant metabolic pathology - K.M. Borovyk; P.Н. Kravchun; O.I. Kadykova (Journal of V. N. Karazin Kharkiv National University: Series Medicine)
Background. The problem of lipid metabolism disorders in patients with coronary artery disease and chronic heart failure, especially with concomitant type 2 diabetes mellitus and obesity, is highly relevant due to their high prevalence, significant contribution to cardiovascular morbidity and mortality, and the complexity of correction. Researching the role of catestatin in this complex clinical scenario opens new perspectives for understanding the pathogenesis of dyslipidemia and developing potential therapeutic strategies.